Permeability evaluation of gemcitabine-CPP6 conjugates in Caco-2 cells - Abigail Ferreira; Sara Moreira; Rui Lapa; Nuno Vale (International Association of Physical Chemists (IAPC), 2020)
Cancer is one of the most alarming diseases due to its high mortality and still increasing incidence rate. Currently available treatments for this condition present several shortcomings and new options are continuously being developed and evaluated, aiming at increasing the overall treatment efficiency and reducing associated adverse side effects. Gemcitabine has proven activity and is used in chemotherapy. However, its therapeutic efficiency is limited by its low bioavailability as a result of rapid enzymatic inactivation. Additionally, tumor cells often develop drug resistance after initial tumor regression related to transporter deficiency. We have previously developed three gemcitabine conjugates with cell-penetrating hexapeptides (CPP6) to facilitate intracellular delivery of this drug while also preventing enzymatic deamination. The bioactivity of these new prodrugs was evaluated in different cell lines and showed promising results. Here, we assessed the absorption and permeability across Caco-2 monolayers of these conjugates in comparison with gemcitabine and the respective isolated cell-penetrating peptides (CPPs). CPP6-2 (KLPVMW) and respective Gem-CPP6-2 conjugate showed the highest permeability in Caco-2 cells.